Mengembangkan Hukum Tuhan: Otoritas Tuhan dan Peran Nalar Manusia dalam Penemuan Hukum Islam - Rulyjanto Podungge (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2016)
This paper discusses the method for pairing the revelation of God and the law of human reason. Islam as a religion throughout the ages must be adaptive, progressive, elastic and supple. The laws they contain must be able to respond to the dynamics of human development, the style of the Quran provides the opportunity for humans to provide a guiding interpretation of the content of the meaning of human civilization. Revelation has been disconnected and the Prophet Muhammad. have died thousands of years ago, the role of reason is needed in the legal solution of people's lives. The use of reason is not just needed now, but since the first days of friends, and even practiced by the Prophet.